2011
DOI: 10.1007/s12088-011-0243-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Moderately Halophilic Pseudoalteromonas Producing Extracellular Hydrolytic Enzymes from Persian Gulf

Abstract: Extracellular hydrolytic enzymes such as amylases, proteases, lipases and DNases have quite diverse potential usages in different areas such as food industry, biomedical sciences and chemical industries, also it would be of great importance to have available enzymes showing optimal activities at different values of salt concentrations and temperature. Halophiles are the most likely source of such enzymes, because not only their enzymes are salttolerant, but many are also thermotolerant. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This interest is due to their capacity to efficiently catalyze a process and show optimal activities at different salt concentrations. Halophiles are the most probable source of extremozymes, since they are also capable of tolerating alkaline pH and high temperatures, as reported by several authors [68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Extremozymes-producing Halophilesmentioning
confidence: 71%
See 1 more Smart Citation
“…This interest is due to their capacity to efficiently catalyze a process and show optimal activities at different salt concentrations. Halophiles are the most probable source of extremozymes, since they are also capable of tolerating alkaline pH and high temperatures, as reported by several authors [68][69][70][71][72][73][74][75][76][77][78][79].…”
Section: Extremozymes-producing Halophilesmentioning
confidence: 71%
“…The authors identified the genera Marinobacter, Virgibacillus, Halobacillus, Geomicrobium, Chromohalobacter, Oceanobacillus, Bacillus, Halomonas, and Staphylococcus as having hydrolase activities of industrial relevance, pointing out the presence of amylases, lipases, and proteases. A new genus of marine bacteria is included among halophiles that are capable of producing extracellular hydrolytic enzymes, according to the research by Ardakani et al [69], who isolated extracellular hydrolytic enzymes from the water and sediments of the Persian Gulf, in that site the isolation of bacteria that produced enzymes belong to the Pseudoalteromonas genera, and the activities include amylase, protease, and lipase.…”
Section: Extremozymes-producing Halophilesmentioning
confidence: 99%
“…Diversity of culturable protease-producing bacteria from many marine environments have been investigated, including seawater and offshore sediments (Ardakani 2012;Zhang et al 2015Zhang et al , 2019, deep sea (Liu et al 2018;Xiong et al 2007;Zhou et al 2009), Antarctic (Cristóbal et al 2011;Olivera et al 2007;Zhou et al 2013), and Arctic (Kim et al 2010;Park et al 2014) regions. Pseudoalteromonas is often an abundant group in these investigations, even the most abundant group in some (Kim et al 2010;Liu et al 2018;Zhang et al 2019).…”
Section: Diversity Of Protease-producing Strains and Their Extracellumentioning
confidence: 99%